PENGARUH KUALITAS PRODUK, PERSEPSI HARGA, DAN LOKASI TERHADAP KEPUTUSAN PENGECER DALAM PEMBELIAN AIR MINUM AQUA KEMASAN GALON DI KECAMATAN NGAMPEL - Ainun Najib, 14.05.51.0091; Sutejo, Bambang (Students' Journal of Economic and Management, 2019)
This study examines the effect of product quality on the consumer decision process in purchasing gallon bottled Aqua water in Ngampel District. the influence of price perceptions on the consumer decision process in purchasing Aqua gallon bottled water in Ngampel District. The effect of location on the consumer decision process in purchasing Aqua bottled gallons in Ngampel Sub-district. The sampling method with purposive sampling technique, the research sample taken in this study were 106 respondents who were buyers of Aqua brand gallon mineral water at Wahid Wholesale Shop Agent in Dempelrejo Village, Ngampel District. Data analysis using multiple linear regression analysis. Hypothesis testing uses t test The results show that product quality has a positive effect on purchasing decisions. Price has a positive effect on purchasing decisions. Location has a positive effect on purchasing decisions